Updating the Debate on Behavioral Competency Development: State of the Art and Future Challenges - Bonesso, Sara; Gerli, Fabrizio; Zampieri, Rita; Boyatzis, Richard E. (Frontiers in Psychology, 2020)
Emotional, social, and cognitive intelligence competencies have been recognized as the most critical capabilities for organizations to acquire at all levels. For this reason, a wide body of research since the 1980s has demonstrated their positive impact on individual performance, career success, and wellbeing across sectors and professional roles, and a large number of theoretical contributions on how these competencies can be effectively developed has emerged over time. We focus attention on the developmental and learning processes of emotional, social, and cognitive intelligence competencies that occur after formal training or educational courses provided by universities or certified organizations and directed to students or practitioners. Specifically, we conduct an exploratory literature review on the existing academic studies in order to identify the scholars and the pieces of research contributing most to the debate under investigation. This article aims at analyzing this body of research through a systematic review of the literature in order to: i) provide a comprehensive critical analysis of the distinctive features of the theoretical and methodological frameworks adopted to develop these competencies; ii) review the contexts in which the training initiatives analyzed by the literature have been delivered and the categories of learner involved; iii) discuss the learning outcomes of these educational programs and how they have been assessed; iv) identify gaps and inconsistencies in the current state of the literature, suggesting promising paths for future research; and v) stimulate insights for educators, human resource managers, executives, and policymakers by organizing and critically analyzing the extant contributions on competency development. This review represents the first attempt to systematize the methodologies of the educational programs for competency development and to assess their effectiveness in order to assist educators and executives in their ongoing efforts to equip students and employees with the relevant skills needed to achieve superior performance in the workplace. At the institutional level, policymakers should promote a dedicated agenda with concrete actions to equip people with emotional and social intelligence competencies.